Noise evaluation of a point autofocus surface topography measuring instrument - Maculotti, Giacomo; Feng, Xiaobing; Galetto, Maurizio; Leach, Richard K. (IOP Publishing, 2018)
In this work, the measurement noise of a point autofocus surface topography measuring instrument is evaluated, as the first step towards establishing a route to traceability for this type of instrument. The evaluation is based on the determination of the metrological characteristics for noise as outlined in draft ISO specification standards by using a calibrated optical flat. The static noise and repeatability of the autofocus sensor are evaluated. The influence of environmental disturbances on the measured surface topography and the built-in software to compensate for such influences are also investigated. The instrument was found to have a measurement noise of approximately 2 nm or, when expressed with the measurement bandwidth, 0.4 nm/√Hz for a single-point measurement.